The Relationship between Academic Procrastination, Self-Regulated Learning and Learning Motivation - Amelia Dhamara Sofyati Halmahera; Eko Darminto (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The research objective is to determined the relationship between academic procrastination with self-regulated learning and learning motivation in high school students. The research was carried out through a quantitative approach with a correlation design. The populations of this study were students of class XI at Senior High School Bojonegoro. The research sample used was class XI students at Senior High School 1 Kedungadem, Senior High School 1 Kepohbaru and Senior High School 1 Sugihwaras as many as 257 students taken through simple random sampling technique. Research data were collected through self-report techniques with academic procrastination scale, self-regulated learning scale and learning motivation scale. The three scales have been tested for validity and respectively have reliability coefficients of 0.917, 0.865, and 0.951. Data analysis was carried out through statistical methods using multiple correlation formulas. The results of analysis prove that there is a significant relationship between academic procrastination with self-regulated learning and learning motivation with a significance score. The results of this study can be used by guidance and counseling teachers as study material to deal with academic procrastination problems that occur among students.